Pemanfaatan Sari Pati Umbi Gadung (Dioscorea hispida Dennst) Untuk Koagulasi Lateks Karet Alam (Hevea brasiliensis) - Lestari, Fitria; Febrianti, Yuli; Wiyono, Joko (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2018)
This research aims to know the utilization of gadung (Dioscorea hispida Dennst) tuber concentrate on natural latex (Hevea brasiliensis) rubber coagulation. The design used in this study was completely randomized design (RAL) with 6 treatments and 4 replications consisting of control and treatment group with concentration of 20 ml, 40 ml, 60 ml, 80 ml and 100 ml. The parameters observed were latex coagulation by administering some concentrations of gadung tuber. One way Anava test with 0.05% significance level showed significant result that is Fcount = 53 and Ftable = 2,77. This shows that gadung tuber concentrate gives a very real effect on latex coagulation. Thus it can be concluded that there is the effect of gadung tuber concentrate to natural rubber latex coagulation.